Construção, calibração e validação de sensores de dissipação térmica para o fluxo de seiva em meloeiro - Silva, Nicolly Kalliliny Cavalcanti (2015)
Agriculture is the productive sector that consumes more water and water is becoming increasingly scarce. In view of this increased demand, in order to improve water this use efficiency, accurate sensors for estimating water consumption by crops have been developed. However, such devices require calibration, especially when are subjected to modifications or when used in field conditions different from those in which were originally developed. Due these facts, the objective of this study was to build, calibrate and validate a sensor for measuring sap flow on melon plants by using the thermal dissipation method (SFDT), as described by Granier (1985). The work was divided into two phases. The first phase was dedicated for the construction and calibration of a sensor, smaller than the one developed by Granier (1985), to be used on estimates of sap flow in melon plants. The SFDT's were built with four different resistances, used as different treatments. Equations relating plant sap to temperature differences measured by the sensor were developed by using a pump for Bourdon type pressure gauge calibration that was connected to a transparent flexible hose in which it was inserted a melon plant stem section. Water was pressurized at 10, 20, 30, 40 and 50 kPa through the hose connected to the stem and collected at the other end by a graduate cylinder. The second stage consisted of an experiment for validation of sensors in a greenhouse, located at Department of Environmental Sciences and Technology – DCAT / UFERSA. A randomized block experimental design, with four treatments and three replications, was used, totaling twelve experimental parcels. Treatments were represented by four different sizes of sinks wires (12, 15, 18 and 21 cm), that resulted in four different resistances (T1) 13.2, (T2) 16.5, (T3) 19.8 and (T4) 23.0 ohms, respectively. The "R" software analysis of variance was used for data analyze. Treatment averages were compared using a 5% significance level Tukey test. There was no difference among sap flow values provided by sensors with different lengths of dissipation wires. The greatest temperature differences were observed with the lower resistance sensor. All built sensors provided similar values of sap flow that were in the same rage of calculated transpiration rate values, indicating that the SFDT are adequate for measuring sap flow through melon plant stem.